2023
DOI: 10.3920/bm2022.0092
|View full text |Cite
|
Sign up to set email alerts
|

The gastrointestinal status of healthy adults: a post hoc assessment of the impact of three distinct probiotics

Abstract: There is a growing awareness that supplementation with probiotic bacteria can impart beneficial effects during gastrointestinal disease, but less is known about the impact of probiotics on healthy subjects. Here, we report the outcomes of a post hoc analysis of recorded daily gastrointestinal events and bowel habits completed by healthy adults participating in a placebo-controlled, single-centre, randomised, double-blind, quadruple-arm probiotic tolerability study. Extensive screening ensured the healthy statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Participants on the probiotic reported 35% fewer loose stools during the intervention period which indicates a potential anti‐diarrhoeal effect and in a Lab4 study with school children (aged 3–10) there was a 44% reduction in the incidence of watery/loose stools 35 . In contrast, in the current IBS study, there were fewer “incomplete” defecations (feeling of incomplete evacuation or failure to defecate) in the probiotic group compared to the placebo group which could be considered to be an “anti‐constipation” outcome and similar outcomes have been observed in a Lab4 study with healthy adults 18 . These data suggest the “normalization” of stool form and this was evidenced by the greater incidence of stools with normal form in the Lab4 group.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Participants on the probiotic reported 35% fewer loose stools during the intervention period which indicates a potential anti‐diarrhoeal effect and in a Lab4 study with school children (aged 3–10) there was a 44% reduction in the incidence of watery/loose stools 35 . In contrast, in the current IBS study, there were fewer “incomplete” defecations (feeling of incomplete evacuation or failure to defecate) in the probiotic group compared to the placebo group which could be considered to be an “anti‐constipation” outcome and similar outcomes have been observed in a Lab4 study with healthy adults 18 . These data suggest the “normalization” of stool form and this was evidenced by the greater incidence of stools with normal form in the Lab4 group.…”
Section: Discussionsupporting
confidence: 78%
“…It has been found that the diversity of the IBS gut microbiota differs from that of healthy subjects 5,6,54–56 particularly in females 57 . Comparison of the baseline alpha diversity of the IBS cohort from this study with that of age, gender and/or geographically matched non‐IBS populations from previous studies with the Lab4 probiotic 18,30 showed the alpha diversity of the IBS population was significantly lower (Figure S8). There was a trend towards higher diversity in the active group at the end of the study, but not the placebo.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations